AMBULATORY BLOOD PRESSURE MONITORING: A NEW DIAGNOSTIC APPROACH FOR DETECTION OF HYPOTENSION IN REFLEX SYNCOPE (SYNABPM 1 STUDY). (June 2022) - Rivasi, Giulia; Groppelli, Antonella; Brignole, Michele; Soranna, Davide; Zambon, Antonella; Bilo, Grzegorz; Pengo, Martino; Sharad, Bashaaer; Hamrefors, Viktor; Rafanelli, Martina; Testa, Giuseppe Dario; Rice, Ciara; et al.
Abstract : Objective: Diagnostic criteria for ambulatory blood pressure monitoring (ABPM) in patients with suspected reflex syncope are lacking. We hypothesized that patients with reflex syncope have a higher prevalence of systolic blood pressure (SBP) drops on ABPM. Design and method: We conducted a retrospective analysis comparing ABPM data from reflex syncope patients and controls, matched by average 24-hour SBP, age, sex and hypertension. Patients with constitutional hypotension, orthostatic hypotension, predominant cardioinhibition or competing causes of syncope were excluded. Daytime and night-time SBP drops (<110, 100, 90, 80 mmHg) were assessed. Hypotensive susceptibility was defined likely or possible for cut-offs achieving the highest sensitivity among those with specificity > 90% and 80–90%, respectively. Findings were validated in an independent sample. Results: In the Derivation cohort, daytime SBP drops were significantly more common in 158 syncope patients than 329 controls. One or more daytime drop < 90 mmHg provided the best diagnostic yield (91% specificity, 32% sensitivity, Odds Ratio [OR] = 4.6, p = 0.001). Two or more-daytime drops < 100 mmHg achieved 84% specificity and 40% sensitivity (OR = 3.5, p = 0.001). Results were confirmed in the Validation cohort: one or more daytime SBP drop < 90 mmHg provided 94% specificity and 29% sensitivity (OR = 6.2, p < 0.001), while two or more daytime SBP drops < 100 mmHg achieved 83% specificity and 35% sensitivity (OR = 3.5, p < 0.001) Conclusions: SBP drops during ABPM are more common in reflex syncope patients than in controls. Cut-off values that may be applied in clinical practice are defined. This study expands the current indications for ABPM to patients with reflex syncope.